PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID MENGGUNAKAN ARTICULATE STORYLINE 3 UNTUK MENGEKSPLOR KEMAMPUAN LITERASI MATEMATIS - Anggraeni, Dewi; Supratman, Supratman; Prabawati, Mega Nur (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The purpose of this study is to discuss the development procedures and the effectiveness of using Android-based interactive learning media using Articulate Storyline 3 on mathematical literacy skills. The method used is Research Development (RD) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Based on research and development, the product ABEKUBA (Cube and Block Learning Application) has been approved for use by material and media experts in the form of an android application. User response to this learning media is positive with very good category. The results of the effect size test on mathematical literacy skills obtained the strong effect category. So that it can be concluded that Android-based interactive learning media using Articulate Storyline 3 is effective for students' mathematical literacy skills.